The Implementation of Classroom Management Principles in Teaching English at Vocational High School 3 Padang - Suparmi (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
The aim of this research was to find out how the teachers implemented principles of classroom management in teaching and learning process at SMKN 3 Padang during teaching and learning process. This is a qualitative research. The data were the result of observation and interview. The participants of this research were three English teachers of SMKN 3 Padang who teach at grade X, XI and XII. The finding of this research indicates that English teachers at SMKN 3 Padang do not implement almost all of the principles of classroom managements during teaching and learning process. They implemented them in three stages of teaching; such as pre-activity, whilst-activity and post activity. Almost all of the principles of classroom management are implemented in whilst-activity. At pre and post-activity, the teacher only implemented three principles, such as warm and enthusiasm, emphasizing on the positive things and building self-discipline. Moreover, the data shows the teachers’ reasons in implementing classroom management. The reason is increasing students’ motivation and achievement. It can be concluded that the English teachers at SMKN 3 Padang should improve their focuses to the principles of classroom management in teaching English. Hopeful, this research can be a significant contribution for English teachers in teaching.